2019
DOI: 10.1177/1527154419876264
|View full text |Cite
|
Sign up to set email alerts
|

A National Scoping Study on Barriers to Conducting and Using Research Among Nurses in the United Arab Emirates

Abstract: It is important that nurses fully engage with the development and use of evidence-based practice so they can influence policy and improve patient care. There are significant challenges in developing nursing research and evidence-based practice in the United Arab Emirates (UAE). Therefore, the UAE Nursing and Midwifery Council formed a Scientific Research Subcommittee to lead the development of nursing research. Following a literature review to assess the status of nursing research in the UAE, the Subcommittee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…Research literacy and engagement of nurses in research have been identified as problematic in the UAE (Al‐Yateem, Almarzouqi, et al, 2020; Al‐Yateem et al., 2019; Al‐Yateem et al., 2019; McCreaddie et al., 2018). Therefore, an informed decision was made to recruit participants who could provide the required data for this study and engage in a relatively complex research process (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research literacy and engagement of nurses in research have been identified as problematic in the UAE (Al‐Yateem, Almarzouqi, et al, 2020; Al‐Yateem et al., 2019; Al‐Yateem et al., 2019; McCreaddie et al., 2018). Therefore, an informed decision was made to recruit participants who could provide the required data for this study and engage in a relatively complex research process (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research suggests that the heterogeneous and peripatetic UAE nursing workforce negatively affects the development of the nursing profession per se and acts as a barrier to future expansion. These workforce characteristics have partly been attributed to the UAE's slow and frequently interrupted progress in important issues on the national nursing agenda, such as specialization, evidence-based practice and research (Al-Yateem et al, 2019, 2020Al-Yateem, Almarzouqi, et al, 2020;McCreaddie et al, 2018).…”
mentioning
confidence: 99%
“…Many barriers to evidence‐based practice have been identified both internationally and locally, including a lack of organisational and leadership support (Al‐yateem et al., 2019; Ay, Gençtürk, & Turan Miral, 2014; Forsman, Rudman, Gustavsson, Ehrenberg, & Wallin, 2010; Runciman et al., 2012). Leadership is essential for the implementation of evidence‐based nursing practice (Bianchi et al., 2018; Castiglione, 2020; Cheng et al., 2018).…”
Section: Leadership For Evidence‐based Nursing Practice In the Uaementioning
confidence: 99%
“…After being established in 2016, the Scientific Research Sub‐committee assessed the status of nursing research in the UAE and identified barriers that hindered the research and evidence‐based agenda (Al‐yateem et al., 2019; McCreaddie et al., 2018). The committee then produced a comprehensive strategic research plan that highlighted the way forward, along with several recommendations for implementation (UAE‐NMC Research Subcommittee, 2018).…”
Section: Leadership For Evidence‐based Nursing Practice In the Uaementioning
confidence: 99%
See 1 more Smart Citation